A comparative study of bipolar experiences in connection with the emotional relations to educational institutes (Training and Practice : Journal of Educational Sciences, 2021)
The topic of this study includes the relations between the bipolar experiences of children aged 5-6, 8-9 and 10-11 and their connection with their educational scenes, kindergarten, and primary school. Their positive and negative experiences are sorted into specific categories based on their drawings and verbally narrated additional content while being continuously compared by age. The psychological phenomenon of attachment is described in the first part of the study and followed by the summary of the empirical research. By the systematization of the results, children’s experiences and narratives of experiences that are crucial in the nature of the attachment to their educational institutions can be determined.